(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Pain is a protective response of an organism forming in answer to the harmful effects of internal and/or external environment. In treatment of pain multiple medications are used; prolonged use of the most of them produces adverse side effects or causes addiction. Generation of now generation medications devoid of the adverse side effects is sure to be a topical problem. To solve the problem, the venom of cobra was fractionated into 7 fractions by chromatography on the Superose 12 column to study their analgesic activity using standard hot plate and acetic acid-induced writhing tests. Some physical-chemical characteristics were determined for fractions S-6 and S-7